Analisis Manajemen Bursa Kerja Khusus (BKK) Sebagai Program Unggulan Penarik Peserta Didik di SMK - Toto Suharso (Media Manajemen Pendidikan, 2023)
The research goals are: Business plan analysis, management organization analysis, management implementation analysis, and BKK management evaluation analysis for specific employment agencies (BKK). This research is qualitative research using interview techniques, observations and documentation. Researchers examine how SMK Batik Sakti 2 Kebumen's analysis of the planning, organization, implementation and evaluation of his BKK management. The analysis used is that of the Miles and Huberman model. Here are the results of this study: BKK was founded and developed based on analysis of problems and existing needs related to distribution of graduates to business/industry. It is also a place for matching graduates and job seekers. The presence of BKK is crucial to the recruitment process and integration of graduates into the world of work. Serving graduates according to the tasks and functions of the BKK section. The BKK is formed through a consultative process among school stakeholders through school-organized activities. BKK management refers to the main functions of general management and includes four main functions: planning, organizing, executing, evaluating and monitoring. A factor hampering the management of BKK is the attitude of students who are independent, unyielding and unprepared to face the world of work.